BRP-170 and BRP190 isoforms of Bruchpilot protein differentially contribute to the frequency of synapses and synaptic circadian plasticity in the visual system of Drosophila - Woźnicka, Olga; Görlich, Alicja; Sigrist, Stephan; Pyza, Elżbieta (Frontiers in Cellular Neuroscience, 2015)
In the first optic neuropil (lamina) of the optic lobe of Drosophila melanogaster, two classes of synapses, tetrad and feedback, show daily rhythms in the number and size of presynaptic profiles examined at the level of transmission electron microscopy (TEM). Number of tetrad presynaptic profiles increases twice a day, once in the morning and again in the evening, and their presynaptic ribbons are largest in the evening. In contrast, feedback synapses peak at night. The frequency of synapses is correlated with size of the presynaptic element measured as the platform size of so-called T-bars, with T-bar platforms being largest with increasing synapse frequency. The large scaffold protein Bruchpilot (BRP) is a major essential constituent of T-bars, with two major isoforms of 190 and 170 kD forming T-bars of the peripheral NMJ synapses and in the brain. In addition to the analysis of cyclic plasticity of tetrad and feedback synapses in wild-type flies, we used TEM to examine daily changes in the size and distribution of synapses within isoform-specific BRP mutants, expressing BRP-190 (BRP170) or BRP-170 (BRP190) only. We found that the number and circadian plasticity of synapses depends on both isoforms. In the BRP190 lacking BRP-190 there was almost 50% less tetrad synapses demonstrable than when both isoforms were present. The lack of BRP-170 and BRP-190 increased and decreased, respectively the number of feedback synapses, indicating that BRP-190 forms most of the feedback synapses. In both mutants, the daily plasticity of tetrad and feedback presynaptic profiles was abolished, except for feedback synapses in BRP190. The oscillations in the number and size of presynaptic elements seem to depend on a different contribution of BRP isoforms in a presynaptic element at different time during the day and night and at various synapse types. The participation of both BRP isoforms may vary in different classes of synapses.